Optimising Communication in the Damage Control Resuscitation- Damage Control Surgery Sequence in Major Trauma Management. Issue 2 (1st June 2012) - Arul, GS; Pugh, HEJ; Mercer, SJ; Midwinter, MJ
Abstract : Damage Control Resuscitation and Damage Control Surgery (DCR-DCS) is an approach to managing severely injured patients according to their physiological needs, in order to optimise outcome. Key to delivering DCR-DCS is effective communication between members of the clinical team and in particular between the surgeon and anaesthetist, in order to sequence and prioritise interventions. Although the requirement for effective communication is self-evident, the principles to achieving this can be forgotten and sub-optimal when unexpected problems arise at critical points during management of challenging cases. A system is described which builds on the 'World Health Organisation (WHO) safer surgery checklist' and formalises certain stages of communication in order to assure the effective passage of key points. We have identified 3 distinct phases: (i) The Command Huddle, once the patient has been assessed in the Emergency room; (ii) The Snap Brief, once the patient has arrived in the Operating Room but before the start of surgery; and (iii) The Sit-Reps, every 10 minutes for the entire theatre team to maintain situational awareness and allow effective anticipation and planning.